2023
DOI: 10.1002/adfm.202304125
|View full text |Cite
|
Sign up to set email alerts
|

Local Oxidation Induced Amorphization of 1.5‐nm‐Thick Pt–Ru Nanowires Enables Superactive and CO‐Tolerant Hydrogen Oxidation in Alkaline Media

Abstract: Low‐dimensional amorphous metallic nanomaterials provide great possibility for creating high‐performance electrocatalysts owing to their conspicuous reacting merits derived from the flexible coordination structures, but remain extremely challenging in synthesis. Herein, this work reports a facile synthesis of carbon‐loaded amorphous 1.5‐nm‐thick Pt–Ru nanowires (NWs) through a local oxidation induced amorphization process. During annealing premade crystalline Pt–Ru NWs/C in air, a local‐oxidation of the oxyphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Recent reports on alkaline HOR catalysts suggest that enhancing the OHBE can accelerate the rate-determined Volmer step through a bifunctional mechanism. This strategy has guided the successful design of highly efficient catalysts such as PtRu [52,53] and Pt/Ni(OH) 2 . [11] However, an excessively high OHBE can lead to active site poisoning and the dissociated adsorption of H 2 by oxygenated spectators, as suggested by the DFT calculation results in this work (Figure 1).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Recent reports on alkaline HOR catalysts suggest that enhancing the OHBE can accelerate the rate-determined Volmer step through a bifunctional mechanism. This strategy has guided the successful design of highly efficient catalysts such as PtRu [52,53] and Pt/Ni(OH) 2 . [11] However, an excessively high OHBE can lead to active site poisoning and the dissociated adsorption of H 2 by oxygenated spectators, as suggested by the DFT calculation results in this work (Figure 1).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…The peaks of PdCo/NC behaved in a negative shift compared to those of Co/NC, once again telling the Co received the electrons from the donator of Pd. The Pd sites with a lack of electrons may not very conducive to the adsorption of *H, which in turn leads to a weakening of the HBE . The N 1s spectrum of Figure S9b features three peaks located at 398.3, 400.6, and 401.6 eV, which belong to pyridinic N, pyrrolic N, and graphitic N bonds, with a relative content of 32.2%, 45.5%, and 22.2%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In subsequent experiments, these porous metal-oxide-coated Ru-based catalysts exhibited improved CO tolerance and robust stability. Xie et al also reported amorphous Pt–Ru nanowires (NWs) in which the small interatomic spaces derived from the disordered bond nets present an H 2 -selective permeability, which spatially obstructs the relatively larger CO molecules to poison the catalytic sites during HOR …”
Section: Strategies For Improving Co Tolerance Of Hor Electrocatalystsmentioning
confidence: 99%
“…Xie et al also reported amorphous Pt−Ru nanowires (NWs) in which the small interatomic spaces derived from the disordered bond nets present an H 2 -selective permeability, which spatially obstructs the relatively larger CO molecules to poison the catalytic sites during HOR. 68 Compared with mainstream electrooxidation and weakening adsorption strategies, such a blocking CO diffusion strategy is essentially independent of the working potential and regulation of the adsorption ability of HOR catalysts, which may play a more important role in developing new types of CO-tolerant HOR electrocatalysts or be combined with the mainstream strategies to synergistically promote CO tolerance. Although there are still some challenges that need to be overcome, without a doubt, this strategy holds great application potential.…”
Section: Mechanismsmentioning
confidence: 99%